Some Aspects of Gained Knowledge of Students in Formation Process of Investigation Methodology - Mahmudqızı, Mahmudova REHIME (Fırat University, 2014)
In the presented article the investigation methodology of formation process of gained knowledge of students is investigated. The author thinks that the gained knowledge is not only the result of student’s knowledge gained at a higher school, but it also depends on the base of school preparation and authors’ specialty level. And here the main problem is that training expresses mutual connection of theory and experience mutual connection of theory and experience and it has complex character as well.

Bumakaledeögrenjilerdebirikim (eldeedilen) bilgisioluşmasısürejininaraştırılmasımetodiğiinjelenir. Müellifşöyleaddediyorki, birikimbilgisiyalnızögrenjininyüksekokuldaeldeettigibilimlerinsonujudegil, hemdeokulhazırlığınıntemeline, öğretmenlerinmeslekdüzeyine, yüksekokulunmaddiselteknikselyöndendurumunaveonunhangiöğrenimgeleneklerinikorumasınabağlıdır. Buradatemelkonuteoriilepratiginilişkisiniyansıtaneğitiminkomplekaraktertaşımasıdır.
ÖGRENJİLERDE BİRİKİM BİLGİSİNİN OLUŞMASI SÜREJİNİN ARAŞTIRILMASI METODİĞİNİN BAZİ YÖNLERİ